Gestão do design como diferencial estratégico competitivo na indústria do vestuário de moda - Souza, Juliana Aparecida de (2013)
The present study aims to contribute to design management as strategic tool on product development for small business. Therefore, concepts were generated about design management which allowed to understand the importance of strategic design be involved in the organization. Adressed also, the great significance of innovation, quality and culture into the context to contemporary organizations. The usage of design management as an element of articulation for small business in fashion wear supplies the empiricism and the dominant improvisation. For this reason, there is a need to create a fashion product using the tecnology developed in this study, of the main competitive advantage is management strategic design to reach the market.